What do we know about spatial entry? - Nicolas Debarsy; Marcus Dejardin (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2008)
In his oft-cited What do we know about entry?, Paul Geroski (1995) gave a survey of empirical works on this central topic regarding industrial organization and, more precisely, market dynamics. Surprisingly, his article remains silent on the spatial dimension of these dynamics. This paper gives first accessory support to some of the Geroskis a-spatial observations with reference to firm entries and exits of a selection of retail and consumer service industries in Belgium over the 1998-2001 period. More important is the proposed application of the Exploratory Spatial Data Analysis (ESDA) that has been developed for in-depth exploring of spatial datasets. Evidences are collected at highly disaggregated geographical and industrial levels. They do not only contribute to a better understanding of the geographical patterns of the industries, but they lead to interesting observations regarding industrial organization and market dynamics by examining the space-time structures of entries and exits. These observations may be considered as an opening tribute towards a spatial extension of what Geroski has presented as stylized facts in his 1995 article.
Keywords: L11; L80; R12; 330; entry; exit; spatial interactions; local market; ESDA; Markteintritt; Marktaustritt; Regionalökonomik; Regionale Wirtschaftsstruktur; Theorie; Belgien